Pengaruh pemberian obat anti tuberkulosis dengan vitamin D terhadap perubahan BTA pada penderita tuberkulosis paru di Kabupaten Pidie - Rina Maulidar; Nurjannah Nurjannah; Aulina Adamy; Iskandar Iskandar (Jurnal SAGO Gizi dan Kesehatan, 2020)
Background: Tuberculosis (TB) is a global health problem, Indonesia had the second rank of the case in the world after India which is the fourth cause of death. Giving vitamin D together with anti-tuberculosis drugs can increase healing proses because vitamin D (anti-microbial immunomodulators) kills Mycobacterium tuberculosis.Objectives: This study aims to measure the effect of giving anti-tuberculosis drugs with vitamin D on changes in AFB in patients with pulmonary tuberculosis.Methods: This study was used a quasi-experiment design, pre-test and post-test control group was doing at 25th March – 25th July 2019. This research has been conducted in Pidie Regency. The intervention group (17 samples with tuberculosis drugs) was given Softgels vitamin D 5000 IU for 4 months, while the control group was only anti-tuberculosis drug therapy. The data were analyzed statistically using the Wilcoxon and Mann Whitney tests at a significance level of 95%.Results: Before the intervention, the BTA status of both the intervention and control group was similar (p= 0.061). After the intervention, there was a decrease in AFB interactions (p= 0.000). There was a decrease in the contribution of AFB in the control group before with after intervention (p= 0.000). There are those who support (p= 0.033) giving vitamin D the acceleration of pulmonary tuberculosis treatment. Conclusion: It is better to administer vitamin D to the successful treatment of pulmonary TB in patients undergoing anti-tuberculosis drug therapy.